Intertextuality manipulation in post-September-eleven American fiction to misinform readership - Mohammad Atawi Saraireh; Thanaa Mohammad Saraireh (IAIN Salatiga, 2020)
This paper investigates how some American writers manipulate intertextuality in American fiction in the wake of the September 11 events. The researchers use Updike’s Terrorist, Miller’s Blindsided, and McBain’s Merely Hate to illustrate this kind of manipulation. An example is cited and discussed in light of the supposed Islamic reference material. The researchers provide a discussion showing how intertextuality is manipulated to misinform readership. The findings indicate that the most employed manipulation strategies are mistranslation, incomplete quotation, out of context Quranic verses, fake information, and distorted ideas about women and the concept of jihad.